2021
DOI: 10.1007/s10639-021-10701-1
|View full text |Cite
|
Sign up to set email alerts
|

University students’ behavioral intention and gender differences toward the acceptance of shifting regular field training courses to e-training courses

Abstract: During the COVID-19 lockdown, all the courses at Imam Abdulrahman Bin Faisal University (IAU) were delivered fully online, including field-training courses. Since there was no previous experience in offering field-training courses in a distance format, the current study aims to identify factors that could impact students’ behavioral intention to accept the e-training approach in teaching field training courses at IAU. In order to gather the data, the researchers designed a questionnaire based on the UTAUT mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
3
10
0
1
Order By: Relevance
“…In another example, Lim (2004) found that significant difference exists in learning motivation between the USA and Korean online learners stemming mostly from cultural orientation and learner characteristics. Again, Alghamdi et al (2022) found significant differences between male and female students regarding effort facilitating conditions, performance expectancy and social influence in relation to intention for usage of e-training. Similarly, Yu and Yu (2021) found after review 21 high-quality articles that females could achieve with Facebook-assisted education significantly better learning outcomes than males.…”
Section: Perceived Value and Engagement In Universitiesmentioning
confidence: 80%
“…In another example, Lim (2004) found that significant difference exists in learning motivation between the USA and Korean online learners stemming mostly from cultural orientation and learner characteristics. Again, Alghamdi et al (2022) found significant differences between male and female students regarding effort facilitating conditions, performance expectancy and social influence in relation to intention for usage of e-training. Similarly, Yu and Yu (2021) found after review 21 high-quality articles that females could achieve with Facebook-assisted education significantly better learning outcomes than males.…”
Section: Perceived Value and Engagement In Universitiesmentioning
confidence: 80%
“…Extant literature is still limited on the application of UTAUT to e-learning acceptance by students [44], particularly during the COVID-19 crisis. Experiences in the Middle East and East Asia [52,53,59,[59][60][61], as well as in several African countries [50,51,55], are particularly represented in literature. Experiences in other parts of the world, such as Europe or America, are comparatively less represented [49,57].…”
Section: The Utaut Framework and E-learning Acceptance During Covid-19mentioning
confidence: 99%
“…These hypotheses were elaborated based on the conclusions drawn in the extant literature on the application of UTAUT to e-learning acceptance, particularly during the COVID pandemic [35][36][37][38][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Indeed, most of the experiences represented in the literature validate the cause-effect relationships between the main constructs of the UTAUT model.…”
Section: Hypothesis 6 (H6) Behavioural Intention Has a Significant Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of posts in an online discussion forum is also a reliable method to provide plentiful resources for the research into gender differences in e-learning since it is a frequently used tool to transmit information and provide peer comments (Ogange et al, 2018 ). A Unified Theory of Acceptance and Use Technology model can be constructed to study gender differences in e-learning to provide references for policy makers and course designers (Alghamdi et al, 2022 ).…”
Section: Limitationsmentioning
confidence: 99%